Awareness of Indonesian Migrant Workers in Paying Zakat: Case Study of Borneo Palm Oil Plantations Samudera Langkon, Marudu, Sabah Malaysia - M Fuad Hadziq; Nargis Ali (IAIN Syekh Nurjati Cirebon, 2025)
Zakat is a fundamental obligation for Muslims, as one of the five pillars of Islam. Therefore, every Muslim must pay zakat annually during the holy month of Ramadan. This research aims to explore the awareness of Indonesian migrant workers regarding the payment of zakat. This study primarily examines the extent of awareness among migrant workers regarding their zakat obligations. Using a qualitative approach, data was collected through in-depth interviews and participatory observations with migrant workers across various industries in Malaysia. The findings reveal that most respondents exhibit a strong awareness of their zakat obligations as a religious duty. Factors such as religious education, personal experiences, and the social environment at the workplace significantly influence the level of awareness. The implications of these findings offer insights for relevant institutions to develop educational and promotional programs aimed at enhancing awareness and compliance with zakat payments among Indonesian migrant workers. This study concludes that religious education, personal experiences, and the social environment at the workplace play a crucial role in shaping migrant workers' awareness of their zakat obligations, and understanding these factors can help design more effective interventions.